Changes in marrow adipose tissue with short-term changes in weight in premenopausal women with anorexia nervosa - Fazeli, Pouneh K. (Eur J Endocrinol, 2019)
OBJECTIVE: In anorexia nervosa, a psychiatric disease characterized by self-induced starvation and a model of chronic undernutrition, levels of subcutaneous (SAT) and visceral (VAT) adipose tissue are low, whereas marrow adipose tissue (MAT) levels are elevated compared to normal-weight women. The reason for this paradoxical elevation of an adipose tissue depot in starvation is not known. We sought to understand changes in MAT in response to sub-acute changes in weight and to compare these changes with those of other fat depots and body composition parameters. DESIGN AND METHODS: We conducted a 12-month longitudinal study including 46 premenopausal women (n=26 with anorexia nervosa and n=20 normal-weight controls) with a mean (SEM) age of 28.2±0.8 years. We measured MAT, SAT, VAT, and bone mineral density (BMD) at baseline and after 12 months. RESULTS: At baseline, SAT (p<0.0001), VAT (p<0.02) and BMD of the spine and hip (p≤0.0002) were significantly lower and vertebral and metaphyseal MAT (p≤0.001) significantly higher in anorexia nervosa compared to controls. Weight gain over 12 months was associated with increases not only in SAT and VAT, but also epiphyseal MAT (p<0.03). Changes in epiphyseal MAT were positively associated with changes in BMD (p<0.03). CONCLUSIONS: In contrast to the steady-state, in which MAT levels are higher in anorexia nervosa and MAT and BMD are inversely associated, short-term weight gain is associated with increases in both MAT and BMD. These longitudinal data demonstrate the dynamic nature of this fat depot and provide further evidence of its possible role in mineral metabolism.